Ethnic minorities' support for redistribution: The role of national and ethnic identity. (February 2020) - Galle, Jolien; Fleischmann, Fenella
According to liberal nationalists, sharing a national identity offers a solution to the growing concern that increasing diversity within Western societies might erode solidarity. Based on the national identity framework, a positive relation between peoples' support for redistribution and their national identification is expected. Partially confirmed among majority group members, the aim of this study is to broaden the perspective and investigate the redistributive attitudes of people with a migration background. Since the social identification of people with a migration background is more complex and tends to be based on belonging to both the nation of residence and a specific ethnic group, we additionally consider the role of ethnic identification. We perform multivariate analyses on data from the Belgian Ethnic Minorities Election Study 2014 (BEMES), a survey conducted among Belgians of Turkish and Moroccan descent. The results confirm our hypothesis about the positive role of national identification. Ethnic identification, on the contrary, is negatively related to support for redistribution and particularly the combination of a low attachment to the country of residence and strong attachment to the country of origin is associated with lower levels of support for redistribution.